Longevity of atraumatic restorations performed by undergraduate dentistry students - Luale Leão FERREIRA; Naiara de Paula FERREIRA-NÓBILO; Cristina GIBILINI; Maria da Luz Rosário de SOUSA
INTRODUCTION:Atraumatic restorative treatment (ART) is a simple technique that enables the treatment of caries with hand tools and without anesthesia where clinic access is lacking.OBJECTIVE: To evaluate the effectiveness of ART conducted in the primary dentition of 4-11-year-olds in 2009 and 2010 by graduate dental students in Piracicaba, SP, and the longevity of restorations at 6 and 12 months.METHOD: Descriptive data analysis was performed. Differences between groups were assessed using the chi-squared test with a 95% confidence interval.RESULT:The success rates of ART were 51.90% at 6 months and 47% at 12 months. Class I ARTs were more successful than class II ARTs at 6 and 12 months (p < 0.001).CONCLUSION: Approximately 50% of ART performed by undergraduates students have succeeded and was significantly better for class I carious lesions at both evaluation time points.